Cross-cultural adaptation and validation of the disease specific questionnaire OQLQ in Serbian patients with malocclusions - Vucic Ljiljana; Glisic Branislav; Kisic-Tepavcevic Darija; Vucic Uros; Drulovic Jelena; Pekmezovic Tatjana (Sciendo, 2016)
Dentofacial disorders may potentially significantly affect the quality of life. Objectives of this study were to validate translated and culturally adapted Orthognatic Quality of Life Questionnaire (OQLQ) on a cohort of Serbian patients with malocclusions.